Synthesis, characterization and application of graphene palladium porphyrin as a nanocatalyst for the coupling reactions such as: Suzuki‐Miyaura and Mizoroki‐Heck. (4th October 2017) - Bahrami, Kiumars; Kamrani, Soheila Nakhjiri
Abstract : The palladium(II)‐coordinated 5, 10, 15, 20‐tetrakis‐(4‐hexyloxyphenyl)‐porphyrin as a macrocyclic palladium complex was covalently grafted to the surface of graphene oxide (denoted as GO‐CPTMS@Pd‐TKHPP). GO‐CPTMS@Pd‐TKHPP was characterized using microscopic and spectroscopic techniques for confirmation of functionalization. The synthesized catalyst was checked in the Suzuki‐Miyaura and the Mizoroki‐Heck coupling reactions. The catalyst is very easy to handle, environmentally safe and economical. Also, this catalytic system shows high catalytic activity and the yields of the products are excellent. Moreover, the suggested catalyst was reusable for five runs with no significant decrease in catalytic activity. Abstract : The palladium(II)‐coordinated 5, 10, 15, 20‐tetrakis‐(4‐hexyloxyphenyl)‐porphyrin as a macrocyclic palladium complex was covalently grafted to the surface of graphene oxide (denoted as GO‐CPTMS@Pd‐TKHPP). GO‐CPTMS@Pd‐TKHPP was characterized using microscopic and spectroscopic techniques for confirmation of functionalization. The synthesized catalyst was checked in the Suzuki‐Miyaura and the Mizoroki‐Heck coupling reactions. The catalyst is very easy to handle, environmentally safe and economical. Also, this catalytic system shows high catalytic activity and the yields of the products are excellent. Moreover, the suggested catalyst was reusable for five runs with no significant decrease in catalytic activity.